Preliminary study on the gratification and continuance intention of Chinese audiences in relation to online film festivals - Yang, Yening; Ahmad Ghazali, Akmar Hayati; Sha'ri, Sharil Nizam; Sun, Jingle (Science Press, 2024)
The emergence of online film festivals has opened up new possibilities for the festival landscape, making the study of the positioning and future development of online film festivals a focal point in the film industry. However, most studies have focused on the significance of online film festivals in curation, economics, or cultural tourism, while overlooking the importance of the audience. This preliminary study aims to understand whether it is relevant to explore gratification among Chinese online film festival audiences and their intention to continue participating in online film festivals in the future.This study fills this gap by examining the gratification levels and continuance intentions of Chinese audiences at the Pingyao International Film Festival (N = 54) through a detailed online survey comprising 37 questions. The results indicate that audiences with higher overall gratification are more strongly inclined to continue participating in online film festivals in the future. Specifically, audiences prioritize their own process gratification and technology gratification provided by online film festivals, while content and social gratification do not significantly influence their willingness to continue participating in the future. This study is based on a small sample size and only covers a portion of the audience demographic. Future research could increase the sample size to obtain more persuasive results. Additionally, this study focuses solely on audience gratification and does not delve into aspects such as motivations. Future research could explore these areas to provide a more comprehensive understanding.